Dating violence perpetration and victimization among high schoolers from public and private schools in Rio de Janeiro, Brazil - Claudia Leite de Moraes; Daniela Porto Faus; Márcia C. Castro; Michael Reichenheim; Washington Leite Junger; Stella Regina Taquette (Cadernos de Saúde Pública)
Dating violence during adolescence is a global public health issue due to its widespread occurrence and negative health consequences. Unfortunately, research addressing this topic in Latin American countries remains limited. Seeking to bridge this gap, the present study estimated the prevalence of both dating violence victimization and perpetration among high schoolers considering sociodemographic factors, exposure to other forms of violence, and school-related characteristics. A total of 539 students participated in the study selected by means of probabilistic sampling from private and public schools in Rio de Janeiro, Brazil. Dating violence was identified using the Conflict in Adolescent Dating Relationships Inventory. Victimization prevalence ranged from 16.7% (sexual) to 94.6% (emotional), whereas perpetration prevalence varied between 9.9% (sexual) and 94.6% (emotional). Boys were more physically victimized (37.2% vs. 24.5%) and perpetrated more sexual abuse (13.7% vs. 6.9%) than girls. Adolescents reporting child abuse, living in violent areas, and those who consumed alcoholic beverages more frequently had greater dating violence prevalence overall. However, some differences between male and female vulnerability characteristics merit debate. These heterogeneous profiles of victimization/perpetration between boys and girls indicate the need for specific dating violence prevention interventions.